2015
DOI: 10.1155/2015/797564
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Patient and Parental Anxiety and Impressions Related to Initial Gastrointestinal Endoscopy: A Japanese Multicenter Questionnaire Study

Abstract: Objective. To assess anxiety among pediatric patients and their parents related to initial gastrointestinal endoscopy. Methods. Patients aged <19 years undergoing initial gastrointestinal (GI) endoscopy and their parents were invited to complete a self-administered questionnaire related to endoscopy in 13 institutions in Japan. Results. The subjects were 128 children, aged 1 month to 17 years. Forty-eight patients (37.5%) underwent esophagogastroduodenoscopy (EGD), 32 (25%) underwent colonoscopy (CS), 39 (30.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…There may be a risk if only one of these perspective is used when bowel cleansing before colonoscopy is planned. Bowel cleansing with PEG was experienced as the most difficult part of the procedure by both children and parents and this result is in accordance with previous quantitative studies [20,21,22,23]. These quantitative studies show difficulties with PEG intake based on a large volume and bad taste, however this study also shows that children were not psychologically prepared for this procedure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There may be a risk if only one of these perspective is used when bowel cleansing before colonoscopy is planned. Bowel cleansing with PEG was experienced as the most difficult part of the procedure by both children and parents and this result is in accordance with previous quantitative studies [20,21,22,23]. These quantitative studies show difficulties with PEG intake based on a large volume and bad taste, however this study also shows that children were not psychologically prepared for this procedure.…”
Section: Discussionsupporting
confidence: 90%
“…The recommended intake of PEG is 25-35 ml/kg bodyweight per hour until clear intestinal fluid is obtained, either orally or by nasogastric tube [19]. Previous quantitative studies show that the intake of large volumes of bad-tasting laxative was the most difficult part of the procedure prior to colonoscopy from both the child's and parents' perspective [10,20,21,22,23]. A limitation of research in this area is that children's and parents' experiences of bowel cleansing have been largely neglected [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Gastrointestinal endoscopy is defined as: the examination which permits direct visualization of the gastrointestinal tract to assess the appearance and integrity of the gastrointestinal mucosa, detect lesions and provide access for therapeutic procedures, it is safe and effective . ( 4) (5) With the advancement of technology, new innovations in medicine and introduction of fiber optic endoscopy and equipments in pediatric, the pediatric endoscopy procedures has been performed effectively and successfully.…”
Section: Introductionmentioning
confidence: 99%
“…1 Moreover, the appropriate dosage of bowel-cleansing agents for children, according to their body size, is unknown. It is difficult for children to ingest large amounts of bowel-cleansing fluid within the limited time required for bowel cleansing prior to pediatric colonoscopy and transanal balloon-assisted enteroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…A Japanese multicenter study revealed that 72% of children who received colonoscopy had difficulty taking a large amount of bowel-cleansing solution. 1 Moreover, the appropriate dosage of bowel-cleansing agents for children, according to their body size, is unknown. In the clinical setting, bowel-cleansing protocols for children are mostly based on the experiences of each medical facility; therefore, this differs widely.…”
Section: Introductionmentioning
confidence: 99%